The Effect of Oxetane as Active Diluent on Cationic UV Curing System of Fluorine-Containing Epoxy Prepolymer - Baihong Chi; Mengying Wei; Yong He (Advances in Polymer Technology)
A series of fluorine-containing polyacrylic epoxy (FPAE) prepolymers with different fluorine content and molecular weight are synthesized by solution free radical polymerization of hexafluorobutyl methacrylate (HFBMA), butyl acrylate (BA), and glycidyl methacrylate (GMA). The synthesized prepolymers show high conversion and low volume shrinkage. The effect of different types of active diluent for the cationic UV curing of FPAE was investigated, among which oxetane exhibits better comprehensive property than epoxy and vinyl ether. The formulations with the optimal ratio of different functionality oxetane combination show good flexibility, adhesion, hydrophobicity, and antistain property.